Anhydrous liquid line of descent of Yamato‐980459 and evolution of Martian parental magmas. (30th September 2013) - Rapp, Jennifer F.; Draper, David S.; Mercer, Cameron M.
Abstract: We report the results of nominally anhydrous equilibrium and fractional crystallization experiments on a synthetic Yamato‐980459 (Y98) bulk composition at 0.5 GPa. These experiments allow us to test a suggested fractional crystallization model, calculated using MELTS by Symes et al. (2008 ), in which a Y98‐like initial liquid yielded a magma closely resembling the bulk composition of QUE 94201. Although the two meteorites cannot be cogenetic owing to their age difference, they are thought to represent bona fide magmatic liquids rather than products of crystal accumulation, as are most Martian basaltic meteorites. Hence, understanding possible petrogenetic links between these types of liquids could be revealing about processes of melting and crystallization that formed the range of Martian basalts. We find that Y98 can, in fact, generate a residual liquid closely resembling QUE, but only after a very different crystallization process, and different degree of crystallization, than that modeled using MELTS. In addition, both the identity and sequence of crystallizing phases are very different between model and experiments. Our fractional crystallization experiments do not produce a QUE‐like liquid, and the crystallizing phases are an even poorer match to the MELTS‐calculated compositions than in the equilibrium runs. However, residual liquids from our experiments define a liquid line of descent that encompasses bulk compositions of parental melts calculated for several Martian basaltic meteorites, suggesting that the known Martian basaltic meteorites had their ultimate origin from the same or very similar source lithologies. These are, in turn, similar to source rocks modeled by previous studies as products of extensive crystallization of an initial Martian magma ocean.